Drosophila fabp is required for light-dependent Rhodopsin-1 clearance and photoreceptor survival - Huai-Wei Huang (Public Library of Science (PLoS), 2021)
Rhodopsins are light-detecting proteins coupled with retinal chromophores essential for visual function. Coincidentally, dysfunctional Rhodopsin homeostasis underlies retinal degeneration in humans and model organisms. Drosophila ninaEG69D mutant is one such example, where the encoded Rh1 protein imposes endoplasmic reticulum (ER) stress and causes light-dependent retinal degeneration. The underlying reason for such light-dependency remains unknown. Here, we report that Drosophila fatty acid binding protein (fabp) is a gene induced in ninaEG69D/+ photoreceptors, and regulates light-dependent Rhodopsin-1 (Rh1) protein clearance and photoreceptor survival. Specifically, our photoreceptor-specific gene expression profiling study in ninaEG69D/+ flies revealed increased expression of fabp together with other genes that control light-dependent Rh1 protein degradation. fabp induction in ninaEG69D photoreceptors required vitamin A and its transporter genes. In flies reared under light, loss of fabp caused an accumulation of Rh1 proteins in cytoplasmic vesicles. The increase in Rh1 levels under these conditions was dependent on Arrestin2 that mediates feedback inhibition of light-activated Rh1. fabp mutants exhibited light-dependent retinal degeneration, a phenotype also found in other mutants that block light-induced Rh1 degradation. These observations reveal a previously unrecognized link between light-dependent Rh1 proteostasis and the ER-stress imposing ninaEG69D mutant that cause retinal degeneration. Author summary Rhodopsins are light-detecting proteins that use retinoids as chromophore co-factors. Rhodopsins are tighly regulated in photoreceptors, as dysfunctional Rhodopsins cause photoreceptor degeneration. The precise mechanisms by which photoreceptors regulate Rhodopsin homeostasis remains unclear. Here, we report that Drosophila fatty acid binding protein (fabp) is a gene required for Rhodopsin-1 (Rh1) protein homeostasis and photoreceptor survival. Specifically, we found that fabp is among the genes induced by an endoplasmic reticulum (ER) stress-imposing Rhodopsin-1 (Rh1) mutant, ninaEG69D, which serves as a Drosophila model for Retinitis Pigmentosa. We further found that fabp induction in ninaEG69D photoreceptors required vitamin A and its transporter genes. fabp was required in photoreceptors to help degrade light-activated Rh1. In the absence of fabp, Rh1 accumulated in cytoplasmic vesicles in a light-dependent manner, and exhibited light-dependent retinal degeneration. These observations indicate that fabp is required for light-induced Rh1 degradation and photoreceptor survival.